Last chance - Hurwitz, Gregg; Hurwitz, Gregg; OverDrive, Inc. (New York : Tor Teen, 2017)
In Creek's Cause, the Rain brothers and their friend Alexandra fight for humanity's survival as everyone over the age of eighteen turns into dangerous, zombie-like beings.
In Creek's Cause, the fight for humanity's survival continues. Everyone over the age of eighteen has been turning into ferocious, zombie-like beings-- and the spores that cause the transformation are not of this Earth. Now a new breed of predatory creature has been spawned, devouring everything in its path. Chance and Patrick Rain and their friend Alexandra may become humanity's only hope for salvation.
"A Tom Doherty Associates book."
Sequel to: The Rains.
Electronic book.
Electronic reproduction.
Keywords: Parasites -- Juvenile fiction; Brothers -- Juvenile fiction; Parasites -- Fiction; YOUNG ADULT FICTION -- Horror; YOUNG ADULT FICTION -- Science Fiction -- Alien Contact; YOUNG ADULT FICTION -- Zombies; Brothers; Parasites; Brothers -- Fiction; Advantage title -- Fiction; Fiction; Juvenile works; Young adult works; Electronic books; Science fiction; Horror fiction; Young adult fiction